Observation and initial impressions of animal production in the southern rangelands - Nicolson, M. (International Livestock Centre for Africa, 1982)
This report discusses the observation and animal production in the southern rangelands of Ethiopia. It explains the way the milk production data is collected, comments on the short comings in and validity and usefulness of the data and it also assesses the constraints within the animal production system in order to draw up a preliminary list of proposals for research.